Obstacle Avoidance Mobile Robot With Ultrasonic Sensors - Qory Hidayati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2017)
AbstractThe robot that can move (mobile robot) is required for observation in difficult circumstances which is difficult to be performed by humans such as extreme temperature, cramped, dark and so on. Robot which is needed, is able to move on its own and can avoid obstacles. Implementation tools through experiments is performed in the laboratory. To determine the direction of the turn is based on the measurement data from the sensor ping ultrasonic range finder, then Arduino will adjust the speed of a DC motor to generate the left and right turn. The test results show mobile robot can move itself and is able to avoid obstacles. When the mobile robot obstacle is stuck in the center with left-right-front, it requires quite a long time to come out.